From rubbish to cultural identity; Making archaeology relevant for the contemporary community - Marwoto, Irmawati (Wacana, Journal of the Humanities of Indonesia, 2019)
Archaeological relevance for the present has become an important issue in the world of archaeology. This paper aims to examine how the biography of artefacts of pottery fragments from the old Banten site, the site of Banten Sultanate of the sixteenth century AD, became a marker of the cultural identity of Banten people today. These pottery fragments were studied using Michael Thompson’s rubbish theory (1979), which observes how the value of objects shifts from transient to rubbish to durable. Using the rubbish theory, archaeological practices that have only been aimed at scientific purposes can be useful for the people of Banten today. This paper will also discuss how people who have been ignored become an important part of archaeological practice and how archaeology can have an economic impact on today’s society.